Long-term analysis of the Antarctic total ozone zonal asymmetry by MERRA-2 and CMIP6 data - Ivaniha, O. (Ukrainian Antarctic Journal, 2020)
Objectives. To analyze ozone monthly mean data from the MERRA-2 reanalysis and CMIP6 model. To determine Antarctic ozone asymmetry climatology for austral spring months (September, October, November) over the 1980–2014 period. Methods. Processing and visualization of the MERRA-2, CMIP6 data on total ozone and ozone partial pressure, following analysis, interpretation, and comparison. Getting 2D (total ozone column) and 3D (ozone partial pressure) monthly mean ozone values for the zonal band (0°–90° S) at pressure levels (1000–0.1 hPa) for each month of the chosen period. Calculating climatology of the total ozone and ozone partial pressure. Comparison of model and reanalysis of results. Results. The amplitude of ozone zonal asymmetry was calculated to provide the monthly, latitudinal, longitudinal and altitudinal analysis. It is shown that the largest ozone zonal asymmetry is observed in spring, especially in October, with dominant wave-1 structure with zonal minimum over 0°–90° W, and maximum over 120°–180° E longitudinal sectors. The area with high ozone content is located at the 40°–80° S zonal band and gradually shifts to the south from September to November. The model underestimates amplitude of ozone zonal asymmetry, especially in October. Conclusions. Latitudinal mean maximums in zonal mean ozone distribution are observed over 62° S, in October over 66° S, and in November over 68° S for MERRA-2 and over 64° S, 65° S and 66° S respectively for CMIP6. The poleward shift of ozone latitude maximum continues until March with decreasing of ozone level, but in April, the shift reverses its direction to equatorward and ozone level starts to increase, however in the model this process is slower. In September the shift again becomes poleward. In the longitudinal distribution wave-1 pattern dominates with a shift of longitude ozone minimum. From September to October the shift is eastward, and from October to November westward by MERRA-2 data and only eastward by CMIP6 data. The highest difference in altitude ozone distribution is observed during October in the stratosphere between ozone zonal minimum and maximum points and reaches approximately 68% (44%) of the zonal average value at 65° S (65.4° S) by MERRA-2 (CMIP6) data. MERRA-2 profiles unlike CMIP6 one show higher location of altitudinal maximum over the zonal minimum and lower over the zonal maximum with the zonal mean in the middle. All three CMIP6 profiles have the same height of altitude maximum.